2019
DOI: 10.1080/08870446.2019.1622014
|View full text |Cite
|
Sign up to set email alerts
|

“I don’t mind being ugly but I don’t wanna have skin cancer”: A qualitative study of attitudes to UV exposure and a facial morphing intervention in men 35 years and older

Abstract: Objectives: Skin cancer is a growing problem globally. Older men have been largely ignored in previous research, even though men may generally be prone to riskier exposure to the sun than women. Past research suggests that appearance-focused techniques such as facial morphing can increase motivations to use sun protection among women of all ages, and younger men. Design: was qualitative, consisting of individual interviews. Method: was semi-structured interviews with 25 older men, to examine attitudes to UV ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It is puzzling that tailored UV imagery increased fear but not threat susceptibility. Theory and past research have both suggested a relationship between fear and susceptibility, and prior meta-analyses have found that personalized UV images increased susceptibility (Persson et al, 2019; Williams et al, 2013). It is important to note that the meta-analysis found a relationship for susceptibility to photoaging rather than skin cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is puzzling that tailored UV imagery increased fear but not threat susceptibility. Theory and past research have both suggested a relationship between fear and susceptibility, and prior meta-analyses have found that personalized UV images increased susceptibility (Persson et al, 2019; Williams et al, 2013). It is important to note that the meta-analysis found a relationship for susceptibility to photoaging rather than skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has found that inclined abstainers can be moved to action through a strategy referred to as implementation intentions. In an implementation intentions intervention, participants write down what sun protective behaviors they intend to perform, when and where they will perform them, and action steps needed to help them successfully implement the behavior (see also, Persson, Grogan, et al, 2018, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects the notion of personhood in which there is ‘a moral and ethical category, tied to the concepts of autonomy, agency and self-determination’ (Sofronas et al, 2018: 407) . This is caused by their perceived loss, but also the uncertainty of their role in future (Gentili et al, 2019; Persson et al, 2019). Gender-based delivery of services has been suggested as a means to remedy some of the aspects mentioned, whilst acknowledging men are one homogenous group (Robertson and Baker, 2017).…”
Section: Discussionmentioning
confidence: 99%